Is drive for muscularity related to body checking behaviors in men athletes? - Leonardo de Sousa Fortes; Maria Elisa Caputo Ferreira; Pedro Henrique Berbert de Carvalho; Renato Miranda
Abstract The aim of this study was to analyze the relationship between drive for muscularity and body checking behaviors in men athletes. Two hundred and twelve Brazilian athletes over 15 years of age participated. We used the Drive for Muscularity Scale (DMS) to evaluate the drive for muscularity. The Male Body Checking Questionnaire was used to assess body checking behaviors. The findings demonstrated a relationship between the "body image-oriented muscularity" subscale of the DMS and body checking behaviors (p = 0.001). The results indicated differences in body checking among athletes with high and low levels of drive for muscularity. We concluded that drive for muscularity was related to body checking behaviors in men athletes.